2021
DOI: 10.13166/jms/143524
|View full text |Cite
|
Sign up to set email alerts
|

The impact of covid-19 pandemic on credit financing of microenterprises and farmer business activity in Poland

Abstract: The novel coronavirus pandemic has hit the Polish economy, including business activity. The paper aims to assess the impact of COVID-19 on the credit financing of microenterprises and farmers in Poland. We analyse investment loans and working capital loans, particularly the changes in the number and value of these loans, the number of loan enquiries, and the share of non-performing loans. The research period covers the two-year period, including the pre-COVID-19 subperiod from March 2019 till February 2020 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Stojczew (2021) notes that tourism is one of the first industries that suffered from the pandemic, which was similar to the crisis in 2009. Zając et al (2021) points out that microentrepreneurs and farmers, due to the scale of their activities, are particularly vulnerable to the negative consequences of the pandemic. According to the ongoing analyzes of the financial data of Polish enterprises (Zimny, 2020a), the transport sector suffered the most in Q2 2020, while the trade and manufacturing were less impacted, and the construction and energy sectors showed just a slight decrease in sales and even improved profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stojczew (2021) notes that tourism is one of the first industries that suffered from the pandemic, which was similar to the crisis in 2009. Zając et al (2021) points out that microentrepreneurs and farmers, due to the scale of their activities, are particularly vulnerable to the negative consequences of the pandemic. According to the ongoing analyzes of the financial data of Polish enterprises (Zimny, 2020a), the transport sector suffered the most in Q2 2020, while the trade and manufacturing were less impacted, and the construction and energy sectors showed just a slight decrease in sales and even improved profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unfortunately, in many cases smaller enterprises, which include microenterprises, struggle with liquidity problems in their current operations. Previous studies have identified the impact of the COVID-19 pandemic on microenterprise credit dynamics (Zając et al, 2021). The credit standing of microenterprises for working capital and overdraft facilities is presented in Figure 3.…”
Section: Dynamics Of Loans To Microenterprisesmentioning
confidence: 99%
“…The key factors influencing the demand for credit among enterprises are levels of their economic and investment activity and interest rates (Calza et al, 2003). The COVID-19 pandemic has increased the uncertainty among SMEs in Poland and negatively affected their credit activity and credit availability (Zając et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The following are potential sources of credit for micro-enterprises: commercial banks; government institutions; microfinance institutions (MFIs); non-governmental organisations (NGOs); savings and credit associations; and informal credit sources (International Labour Organisation, 2023). However, it is noted that commercial banks normally favour large loans over small ones (Adelekan, et al, 2019;Zaj c, et al, 2021) and have misgivings about the rural poor, particularly women and youths who are classified as high risk clients. On the other hand, in order to enhance micro-enterprises' ability to access formal credit lines, the micro-business owners should increase their financial knowledge (Liu, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%